Retinal Thickness and Morphology Changes on OCT in Youth with Type 2 Diabetes - Mihai Mititelu, MD, MPH; Diane Uschner, PhD; Lindsay Doherty, PhD; Petter Bjornstad, MD; Amitha Domalpally, MD, PhD; Kimberly L. Drews, PhD; Rose Gubitosi-Klug, MD, PhD; Lynne L. Levitsky, MD; Jeong W. Pak, PhD; Neil H. White, MD; Barbara A. Blodi, MD (Ophthalmology Science, 2022)
Objective: To evaluate changes in retinal thickness and morphology using OCT in youth with type 2 diabetes (T2D) and to identify systemic biomarkers correlating with these changes. Design: Retrospective subgroup analysis of a prospective study. Participants: Participants who underwent OCT imaging in the Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) trial and its follow-up study TODAY2. Methods: In 2010–2011 (TODAY) and 2017–2018 (TODAY2), 6 × 6-mm macular volume OCT scans were acquired, segmented, and analyzed to generate total retinal thickness, inner retinal thickness, and outer retinal thickness. The main retinal morphologies graded were intraretinal cystoid spaces, subretinal fluid, and posterior vitreous detachment (PVD). Main Outcome Measures: Changes in total and individual retinal layer thickness and development of abnormal vitreomacular morphology between TODAY and TODAY2. Results: Participants had a mean age of 17.9 ± 2.4 years and glycated hemoglobin (HbA1c) of 8.2 ± 2.8% in TODAY and a mean age of 25.0 ± 2.4 years and mean HbA1c of 9.5 ± 2.8% in TODAY2. Longitudinally between assessments, there were overall decreases in outer retinal thickness from 167.2 ± 11.5 microns to 158.4 ± 12.8 microns (P < 0.001) and in photoreceptor thickness from 30.3 ± 2.9 microns to 29.8 ± 4.1 microns (P = 0.04) in the central subfield, while in the inner subfield, we noted a decrease in outer retinal thickness from 150.5 ± 10.1 microns to 144.9 ± 10.5 microns (P < 0.001) and an increase in inner retinal thickness from 136.9 ± 11.5 microns to 137.4 ± 12.6 microns (P = 0.01). Multivariate analysis showed that in the center subfield, HbA1c increases were associated with increases in total retinal thickness (r: 0.67, P = 0.001), whereas fasting glucose was positively correlated with inner retinal thickness (r: 0.02, P = 0.02). In the inner subfield, both systolic (r: −0.22, P < 0.001) and diastolic (r: −0.22, P = 0.003) blood pressures were negatively correlated with total retinal thickness. There was an increase in PVD (18.9%) and cystoid spaces (4.2%). Conclusions: Youth with T2D develop retinal thickness changes on OCT, including increases in total retinal and inner retinal thickness in the center subfield that correlate with HbA1c and fasting glucose, respectively. Taken together with the increased prevalence of abnormal vitreomacular morphology in this cohort at risk, these findings emphasize the importance of controlling risk factors to prevent the development of sight-threatening retinal complications.